Integrated Second Five-Year Plan 1965-61 Punjab State - Government of Punjab (Government of Punjab, 1957)
The Punjab State Integrated Second Five-Year Plan (1956-61) presents a comprehensive framework for the state’s socio-economic transformation through strategic investments across multiple sectors. With a total proposed expenditure of ₹170 crores, the Plan prioritized agriculture, irrigation, power, industry, transport, education, health, and social welfare. Key agricultural initiatives included increased food production, minor irrigation projects, and enhanced animal husbandry and dairying, supported by cooperative programs and land consolidation efforts. The Bhakra-Nangal Multipurpose Project emerged as a centerpiece, providing irrigation and electricity to boost agricultural productivity. Industrial development focused on textiles, handicrafts, and cooperative industries to foster rural employment. Infrastructure investments emphasized road construction to improve market connectivity. Social services targeted educational expansion, teacher training, healthcare facility upgrades, and welfare programs for Scheduled Castes, Tribes, and women. Overall, the Plan aimed to enhance economic output, improve living standards, and empower communities, laying the foundation for sustainable and inclusive growth in post-independence Punjab.
Punjab
Punjab
Keywords: Punjab Development; State Plan; Agriculture Enhancement; Irrigation Projects; Bhakra-Nangal Project; Power Generation; Industrial Development; Transport Infrastructure; Education Initiatives; Health Services; Social Welfare; Rural Development